PRAGMATIC FEATURES OF SUBCOLLOQUIAL PHRASEOLOGICAL UNITS IN FRENCH AND UZBEK - Nodirjon Otaqulov (Modern American Journals, 2025)
This scientific article provides a comprehensive analysis of the pragmatic features of subcolloquial phraseological units in French and Uzbek, based on both theoretical and applied studies in modern linguistics. Within the scope of the research, the role of these units in the language system has been identified, along with their frequency and activity in spontaneous spoken discourse. Their communicative-functional load, social-discursive role, and stylistic adaptability are examined in detail. In particular, the study focuses on how subcolloquial phraseologisms are pragmatically realized in speech acts and the mechanisms through which they express the speaker's social status, attitude, and emotional involvement. Furthermore, the article analyzes how these units are recorded in lexicographic sources, exploring the criteria for their selection, their affiliation to specific functional and stylistic layers, and their use across various communicative contexts. The findings of this study contribute to a deeper understanding of the linguopragmatic nature of phraseological units and provide new insights into their role and function within informal verbal interaction.
Keywords: Colloquial, subcolloquial, phraseology, functional–stylistic, pragmatic, communicative, expressive, colloquial speech.